Observation of Inquiry-based Science Learning in Melbourne (Overseas Training School Victoria, Australia 2015) - Diah Pitaloka Handriani (Universitas Sebelas Maret, 2015)
Observation, interview, and a review of documents of Inquiry-based science learning in the School of Melbourne, Victoria Australia shows that science-learning activities take place both in the classroom and outside the classroom and learn science through the phenomenon as well as natural phenomena that occur around the learners either contextually or abstractly. The scientific process is very dominating in learning activities, simple but very meaningful to the life of learners. The learners do not instantly obtain independent discovery concept during the learning process, but the Inquiry-based learning activities are repeated, collaborated and integrated between the subject matter, which was applied science and made memory endurance and retention of learners in finding the concept very independently and meaningful. Skills in expressing the ideas, opinions, and asking good questions to other learners and teachers are freely allowed, therefore the basic principle of Inquiry Based Science Learning, which is close to the skills process are not limited to the teacher’s skills in asking a high-level questions. However, it is the learners who conveyed ideas and opinions during learning activities. Science curriculum used is AusVELS Science, covering Understanding Science, Science as Human Endeavour, and Science Inquiry Skills. It is relevant to the Curriculum in 2013 that applied in Indonesia with competency-based scientific approach covering spiritual core competencies, Social Core Competence, Knowledge Core Competence, and skills Core Competencies.Keywords: Science Learning, Inquiry, Melbourne, Overseas Training